1987
DOI: 10.1111/j.1432-1033.1987.tb11197.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of thyroid protein kinase C

Abstract: Thyroid protein kinase C (PKc) from cytosols of porcine and rat thyroid glands has been characterized using histone H1 or endogenous proteins as substrates. As in many other tissues histone HI is by far the preferred exogenous substrate of thyroid PKc. Kinetic studies with H1 showed that, compared to rat thyroids, porcine glands are particularly rich in PKc, the predominant kinase activity in this tissue. The CAMP-dependent protein kinase (PKa) level, on the contrary, is very similar in both rat and porcine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…We also demonstrated that recombinant PKCα and βII directly phosphorylate His-CUGBP1 in an in vitro kinase reaction. Several PKC isozymes translocate to the nucleus upon activation and regulate nuclear events such as transcription, splicing and mRNA stability via phosphorylation of nuclear targets such as lamin B and histone H1 (Fields et al, 1988;Martelli et al, 2006;Martelli et al, 2003;Omri et al, 1987). It is also possible that CUGBP1 is phosphorylated in the cytoplasm and is efficiently translocated to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that recombinant PKCα and βII directly phosphorylate His-CUGBP1 in an in vitro kinase reaction. Several PKC isozymes translocate to the nucleus upon activation and regulate nuclear events such as transcription, splicing and mRNA stability via phosphorylation of nuclear targets such as lamin B and histone H1 (Fields et al, 1988;Martelli et al, 2006;Martelli et al, 2003;Omri et al, 1987). It is also possible that CUGBP1 is phosphorylated in the cytoplasm and is efficiently translocated to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…All incubations were carried out at 30°C for 3 min. Total endogenous protein phosphorylation was measured on samples (50 pll) of the reaction mixture spotted on 2.1 cm-diameter filter paper discs (Whatman 3MM) and processed as previously described (Omri et al, 1987). The remaining fraction (250 ,1) was mixed with an equal volume in lysis buffer containing the following; 10 mM Tris/HCl, pH 7.4, 50 mM NaCl, 1 % Nonidet P40, 0.5 % sodium deoxycholate, 5 mM EGTA, 1 mg/ml BSA, 1 mM phenylmethanesulphonyl fluoride, 100 units/ml aprotinin, 1 #sg/ml each of antipain, leupeptin and pepstatin, and 1 mM orthovanadate, 25 mM NaF, 5 mM p-nitrophenyl phosphate and 10 mM sodium pyrophosphate.…”
Section: Mesanglal-cell Culturesmentioning
confidence: 99%
“…We evaluated PKCζ activity by measuring the incorporation of 32 P into specific substrate in aliquots in which the reaction had been stopped, on 2.1‐cm diameter Whatman filter discs, by dropping the discs into 10% trichloroacetic acid solution supplemented with 0.1 m m ATP as a carrier. Filter discs were decontaminated as described previously (Omri et al . 1987).…”
mentioning
confidence: 99%